Pengaruh Kualitas Pelayanan dan Fasilitas terhadap Minat Berkunjung Kembali melalui Kepuasan Konsumen Hotel Comercial Bizpark - Prakoso, Diki; Tanjung, Ahmad Albar (Fakultas Ekonomi Universitas Samudra, 2025)
The research identifies the influence of service quality and facilities on intention to revisit through consumer satisfaction at hotels in the Commercial Bizpark Kualanammu complex. The sample includes 100 respondents selected using accidental sampling technique. The results of the SEM-PLS analysis show that the quality of services and facilities is proven to have a direct positive and significant effect on consumer satisfaction; as well as, service quality, facilities and customer satisfaction have been proven to have a positive and significant effect on interest in returning to visit. Indirectly, the quality of services and facilities has a positive and significant effect on interest in returning to visit through consumer satisfaction. It is expected that the results of this research will further help maintain facilities and improve the quality of hotel services.